1986
DOI: 10.7326/0003-4819-105-4-503
|View full text |Cite
|
Sign up to set email alerts
|

Higher Risk of Lung Cancer in Chronic Obstructive Pulmonary Disease

Abstract: To assess the risk of lung cancer in patients with chronic obstructive pulmonary disease, we matched, on the basis of age, sex, occupation, and smoking history, 113 persons ("cases") who had a forced expiratory volume in 1 second (FEV1) of 70% or less of predicted normal with 113 control persons who had an FEV1 of 85% or more. All persons were observed from 1973-74 through 1984 for a diagnosis of lung cancer, death from lung cancer, and death from any cause. At entry, subjects had an age range of 45 to 59 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
198
3
7

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(217 citation statements)
references
References 17 publications
9
198
3
7
Order By: Relevance
“…This is an important observation that may have implications in the design of chemoprevention trials for smokers at risk of lung cancer. COPD is an established independent risk factor for lung cancer development, and for any level of tobacco exposure, patients with COPD are at greater risk for lung cancer development than smokers without COPD (Skillrud et al, 1986). Several studies have reported aberrant over-expression of the COX-2 protein in lung and other cancers, while therapy with inhibitors of COX-2 is associated with reduced occurrence of certain cancers (reviewed by (Sandler and Dubinett, 2004) and (Harris, 2007)).…”
Section: Discussionmentioning
confidence: 99%
“…This is an important observation that may have implications in the design of chemoprevention trials for smokers at risk of lung cancer. COPD is an established independent risk factor for lung cancer development, and for any level of tobacco exposure, patients with COPD are at greater risk for lung cancer development than smokers without COPD (Skillrud et al, 1986). Several studies have reported aberrant over-expression of the COX-2 protein in lung and other cancers, while therapy with inhibitors of COX-2 is associated with reduced occurrence of certain cancers (reviewed by (Sandler and Dubinett, 2004) and (Harris, 2007)).…”
Section: Discussionmentioning
confidence: 99%
“…Independent of smoking behaviour, family history and occupational exposure, lung cancer risk is increased in patients with limited airway flow (Skillrud et al, 1986). Pulmonary surfactant is essential for normal lung function and provides several functions related to local airway conditions, such as enhancement of mucocilliary clearance, improvement of airway stability, encoating, deposition and retention of inhaled substances and particles as well as interaction with infectious agents.…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic factors may strongly mediate the risk among those who are exposed to carcinogens, as only 11% of the tobacco smokers ultimately develop lung cancer (Amos et al, 1999). In patients with impaired lung function, incidence and mortality of lung cancer is increased, independent of smoking habits, age and family history (Skillrud et al, 1986). Thus, in response to environmental mutagens the individual variability may be mediated by local factors of the airways.…”
mentioning
confidence: 99%
“…It was shown that the relative risk for smokers to be affected by lung cancer, when they suffered from obstructive ventilation disorder (Skillud et al, 1987) was significantly higher than that of comparative groups with normal lung-function parameters.…”
Section: Protecting Micronutrients In Meat With Respect To Cancermentioning
confidence: 92%